Comparison of Transobturator Tape Surgery Using Commercial and Hand Made Slings in Women with Stress Urinary Incontinence - Ciftci, Seyfettin; Ozkurkcugil, Cuneyd; Ustuner, Murat; Yilmaz, Hasan; Yavuz, Ufuk; Gulecen, Turgay (Urology Journal, 2015)
Purpose: To compare the complications and success rates of hand-made sling with commercial sling used in transobturator tape (TOT) surgery. Materials and Methods: From 2008 to 2010, hand-made slings were used in TOT surgery, whereas commercial slings were used from 2010 to 2013 in our clinic. Overall 102 patients were included in the study. Patients were categorized into 2 groups: group 1 had hand-made (polypropylene monofilament) slings, while group 2 had commercial slings (polypropylene monofilament). We retrospectively reviewed 1-year follow-up results of the whole cohort. Ages, body mass indexes, menopausal status, operation time, cost of sling, success of operation and complications were recorded. All these data were compared between the 2 groups. Results: There were 41 patients (54.29 ± 9.88 years) in group 1 and 61 patients (52.82 ± 9.85 years) in group 2. Menopausal status and body mass index (28.1 vs. 29.2 kg/m² respectively) were similar for both groups. Previous history of incontinence or pelvic organ prolapse surgery (P = .046), mean duration of the procedure (P = .001), and vaginal extrusion rate (P = .016) were significantly lower in group 2. The cost of the sling was higher in group 2 than in group 1. There was no significant difference in success of operation between the groups (P = .319). Conclusion: According to our results, hand-made mesh is a viable option in TOT surgery with similar efficacy, but surgeons should be careful in terms of vaginal extrusion.